2022
DOI: 10.3389/fgwh.2022.837358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Integration of Family Planning Into HIV Services on Contraceptive Use Among Women Accessing HIV Services in Low and Middle-Income Countries: A Systematic Review

Abstract: There is substantial unmet need for family planning (FP) among women living with HIV (WLHIV), leading to unintended pregnancies and may contribute indirectly to increasing the risk of transmission of HIV. This review aims to determine whether integration of FP into HIV testing and care results in increased use of contraception, a reduction in unmet need for FP, improved use of safer conception methods and a reduction in unintended pregnancies in low and middle-income countries. A systematic review was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…[22,23] Prior studies have demonstrated that service integration increases the uptake of modern contraceptives among HIV-positive women [16, 17,22]. A systematic review study by Grant-Maidment and colleagues reported 8% higher contraceptive use in integrated than on non-integrated facilities [17]. The difference in contraceptive prevalence in women on ART and those not in ART in this study is smaller than the expected impact of service integration observed elsewhere.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…[22,23] Prior studies have demonstrated that service integration increases the uptake of modern contraceptives among HIV-positive women [16, 17,22]. A systematic review study by Grant-Maidment and colleagues reported 8% higher contraceptive use in integrated than on non-integrated facilities [17]. The difference in contraceptive prevalence in women on ART and those not in ART in this study is smaller than the expected impact of service integration observed elsewhere.…”
Section: Discussionmentioning
confidence: 53%
“…The increase in modern contraceptives may be attributed to family planning and HIV services integration and or reduced desire for more children following HIV diagnosis. [22,23] Prior studies have demonstrated that service integration increases the uptake of modern contraceptives among HIV-positive women [16, 17,22]. A systematic review study by Grant-Maidment and colleagues reported 8% higher contraceptive use in integrated than on non-integrated facilities [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unmet need for contraception among WLWH remains high because of many intersecting individual [ 15 , 16 ], societal [ 17 ] and structural barriers [ 18 ]. These barriers include insufficient knowledge about family planning (FP), negative family planning beliefs, fear of side effects, partnership dynamics, long wait times at clinics, and stockouts of contraceptive commodities [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%